2017
DOI: 10.1371/journal.pgen.1006542
|View full text |Cite
|
Sign up to set email alerts
|

A Gap Junction Protein, Inx2, Modulates Calcium Flux to Specify Border Cell Fate during Drosophila oogenesis

Abstract: Intercellular communication mediated by gap junction (GJ) proteins is indispensable during embryogenesis, tissue regeneration and wound healing. Here we report functional analysis of a gap junction protein, Innexin 2 (Inx2), in cell type specification during Drosophila oogenesis. Our data reveal a novel involvement of Inx2 in the specification of Border Cells (BCs), a migratory cell type, whose identity is determined by the cell autonomous STAT activity. We show that Inx2 influences BC fate specification by mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 50 publications
(63 reference statements)
5
24
0
Order By: Relevance
“…We highlighted 14 representative genes involved in epithelial development (GO: 0060429, P adj = 1.101e −5 ), the highly enriched GO term in this cluster. These include markers for border cell migration, such as sn, jar, and Inx2 [15,[87][88][89]. We also detected in this cluster the expression of Cad99C, which has been reported in several MBFCs and anterior-migrating centripetal cells [83].…”
Section: Expression Profiles Of Migrating Border and Centripetal Cellssupporting
confidence: 69%
“…We highlighted 14 representative genes involved in epithelial development (GO: 0060429, P adj = 1.101e −5 ), the highly enriched GO term in this cluster. These include markers for border cell migration, such as sn, jar, and Inx2 [15,[87][88][89]. We also detected in this cluster the expression of Cad99C, which has been reported in several MBFCs and anterior-migrating centripetal cells [83].…”
Section: Expression Profiles Of Migrating Border and Centripetal Cellssupporting
confidence: 69%
“…We highlighted 14 representative genes involved in epithelial development (GO : 0060429, P adj = 1.101e −5 ), the highly enriched GO term in this cluster. These include markers for border cell migration, such as sn, jar, and Inx2 [25,35,45,79]. We also detected in this cluster the expression of Cad99C, which has been reported in several main body follicle cells, and anterior-migrating centripetal cells [21].…”
Section: Expression Profiles Of Migrating Border and Centripetal Cellssupporting
confidence: 69%
“…We therefore conclude that the gap junction channels composed of INX5 in αβ neurons are critical for ARM retrieval (Fig 7). A recent study showed that the gap junction protein INX2 regulates calcium transmission across the follicle cells during Drosophila oogenesis[37]. In addition, INX1/INX2 induces calcium oscillations in the glial cells of the blood-brain barrier (BBB), enabling signal amplification and synchronization across the BBB in fruit flies[26].…”
Section: Discussionmentioning
confidence: 99%